SOCIAL MEDIA MARKETING ON BRAND AWARENESS LOCAL INDONESIAN COSMETIC SOMETHINC - Silfitri; Daniel Hermawan (Politeknik Ubaya, 2023)
Somethinc is a local beauty product company that, despite only having been established for less than 3 years, is among the 50 most popular local brands according to the survey published by Katadata.co.id in 2020. Social media marketing is used as a variable within this research, due to a significant rise of awareness towards beauty products due to social media platforms. This research aims to measure the impact of social media marketing on Somethinc's brand awareness. Quantitative research methods were used in this study, using questionnaires as a means to gather data from 101 respondents who fulfilled the research criteria and the Cochran formula. Multiple regression analysis is used to determine the impacts of every indicator towards brand awareness, with F-test and t-test as methods for hypothesis testing. This study has found that social media marketing indeed has an impact on the brand awareness of Somethinc. However, when each indicator was tested individually, content creation and connection dimensions were shown to have a significant impact on Somethinc’s brand awareness, while the dimension of content sharing scored the lowest.